COMPARATIVE STUDY OF MUSCLE STRENGTH, COORDINATION ABILITY AND HOCKEY SKILLS OF HOCKEY PLAYERS PRACTICING ON ASTROTURF GROUND AND CLAY GROUND - Sukhdeve, Rakeshkumar; Raut, Raju Mahadev (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Field hockey is a dynamic sport that requires a unique combination of muscular strength, coordination and technical skill. Over the years, the game has undergone a lot of changes, with the most notable change being the transition from traditional grass fields to synthetic astro turf surfaces. This change has not only changed the way the game is played, but has also affected the physical and technical demands placed on the players. Astro turf, with its faster ball speeds, consistent surface and low friction, has become the standard for international and professional competitions. However, in many regions, especially at the grassroots level, traditional grass fields remain the primary training and playing surface due to economic and infrastructure constraints. This disparity raises important questions about how different playing surfaces affect players' physical characteristics and skill development.